KEGIATAN EDUKASI BAGI PETERNAK SAPI SEBAGAI UPAYA PENANGGULANGAN WABAH DI KABUPATEN MERAUKE - Irianto, Apri; Gebse, Yolanda; Praptiwi, Irine Ike; Nurcholis, Nurcholis; Daoed, Denvy Meidian; Hutabarat, Desmina Kristiani; Salamony, Syetiel Maya; Lesik, Maria Magdalena Nay Nadu (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Cattle farming in Merauke Regency is still mostly simple, maintained semi-intensively and extensively. Most farmers keep livestock only as savings. Most still depend on nature, especially in the provision of feed, and leave livestock for days in the forest, this will have an impact on the health and productivity of livestock, and this is thought to be one of the causes of the high livestock mortality rate in Merauke Regency by mid-2024. The participation of all parties, including farmers, government and academics, is needed to prevent an increase in mortality due to the outbreak. The exact cause of the massive mortality is not yet known, so educational assistance is required by the community, especially farmers. The method used by the academics, in this case, lecturers and students, is to hold discussions with the farming community in one of the villages that has a large enough cattle population but has not paid attention to maintenance management. The discussion results became a reference for the academic team to develop a socialisation and training programme to solve the problems farmers face. The programme included the distribution of vitamins and dewormers, feed fermentation training, socialisation of manure processing into fertiliser and socialisation of cattle health assessment. The activities were carried out for 6 months, with monitoring and evaluation. The results of this service activity are, that the level of knowledge and understanding of farmers is increasing regarding the need for health care and the application of good management for livestock to increase productivity and reduce the negative impacts that can be caused. Another benefit is the improvement of skills in managing feed ingredients, thus reducing dependence on nature.